Benefits of a Guided Motor-Mental Preperformance Routine on Learning the Basketball Free Throw. Issue 1 (February 2020) - Moradi, Jalil
While past research has shown the benefits of preperformance routines (PPRs) on athletes' performances, only a few studies have addressed PPR effects on novices' learning or performance. This study investigated the effect of motor-mental PPR on learning the basketball free throw. We categorized 45 undergraduate male students into three 15-session training groups receiving (a) a five-step PPR based on Singer's model, (b) a self-regulation PPR, and (c) no PPR, but only a basketball free throw performance (control group). One week later, we conducted retention and transfer testing. A repeated measures analysis of variance and two-way mixed design analysis of variance showed that, in the acquisition and test phases, the five-step PPR group performed better than the other two groups ( p  < .001), and there was no significant difference between the self-regulation PPR and control groups. The results also showed that, in accordance with the specificity of practice hypothesis, participants' performance decreased significantly on transfer testing when PPR was removed from the experimental groups. A well-guided motor-mental PPR was superior to a self-regulated PPR for novices learning this basketball skill, probably because it increased the participants' concentration during acquisition and helped them learn it as part of a motor pattern.